ANALISIS PENGARUH TATA KELOLA PERUSAHAAN TERHADAP PENGUNGKAPAN MODAL INTELEKTUAL (Studi Empiris Pada Perusahaan Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Benrindang Latusura; Dul Muid (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of corporate governance on intellectual capital disclosure. The variables used in this study are board size, proportion of independent commissioners, blockholder ownership, and government ownership as independent variables and disclosure of intellectual capital as the dependent variable. This study also uses three control variables, namely SIZE, ROA, and LEV.This study uses a sample of banking companies in 2017-2019 with a total sample of 132 samples. Sampling was based on a purposive sampling method that followed certain criteria. Multiple linear regression analysis is the analytical method used in this study.The results of this study indicate that board size and government ownership have a negative and insignificant effect on intellectual capital disclosure. But found that the proportion of independent commissioners had a positive and significant effect on intellectual capital disclosure.